2014
DOI: 10.1093/pch/19.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of suspected and confirmed bacterial meningitis in Canadian children older than one month of age

Abstract: Penicillin susceptible (MIC ≤0.06 µg/mL) Penicillin G or ampicillin Cefotaxime, ceftriaxone Penicillin resistant (MIC ≥0.12 µg/mL) AND ceftriaxone or cefotaxime susceptible (MIC ≤0.5 µg/mL) Ceftriaxone or cefotaxime Meropenem Penicillin resistant (MIC ≥0.12 µg/mL) AND ceftriaxone or cefotaxime intermediate or fully resistant (MIC ≥1.0 µg/mL) Ceftriaxone or cefotaxime AND vancomycin* *Consult an infectious disease expert Meropenem Neisseria meningitidis Penicillin susceptible (MIC <0.12 µg/mL) Penicillin G or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Such a strategy would bring the UK in line with recommendations from other developed countries, for example Canada,9 the USA10 11 and Netherlands 12. In these countries the empirical antibiotic recommendation for meningitis is to use a penicillin in addition to cefotaxime in the 1st month of life, but not beyond this age.…”
Section: Rational Antibiotic Prescribingmentioning
confidence: 99%
“…Such a strategy would bring the UK in line with recommendations from other developed countries, for example Canada,9 the USA10 11 and Netherlands 12. In these countries the empirical antibiotic recommendation for meningitis is to use a penicillin in addition to cefotaxime in the 1st month of life, but not beyond this age.…”
Section: Rational Antibiotic Prescribingmentioning
confidence: 99%
“…[19][20][21] It has been reported that the predominant bacteria causing pediatric PM are E. coli K1, S. agalactiae, and L. monocytogenes in neonatal patients and N. meningitidis, S. pneumoniae, and H. influenzae type b in patients beyond the neonatal period. 10,22 In our study, the etiology was identified in 42.5% of the patients upon combinatory tests by CSF culture and multiplex PCR assay. Therefore, a multiplex PCR assay is advised to perform with CSF culture in combination to improve the pathogenic diagnosis in patients with PM.…”
Section: Journal Of Pediatric Infectious Diseasesmentioning
confidence: 55%
“…У пацієнтів з імуносупресією з огляду на можливість лістеріозної інфекції до комбінованої терапії також додається ампіцилін. Меропенем рекомендується використовувати як препарат другого ряду [8,9]. У випадках госпітального інфікування серед можливих етіологічних чинників зростає роль резистентних грамнегативних бактерій і стафілококів.…”
Section: бактеріальний менінгітunclassified